2012
DOI: 10.5194/os-8-1123-2012
|View full text |Cite
|
Sign up to set email alerts
|

A global algorithm for estimating Absolute Salinity

Abstract: Abstract. The International Thermodynamic Equation ofSeawater -2010 has defined the thermodynamic properties of seawater in terms of a new salinity variable, Absolute Salinity, which takes into account the spatial variation of the composition of seawater. Absolute Salinity more accurately reflects the effects of the dissolved material in seawater on the thermodynamic properties (particularly density) than does Practical Salinity.When a seawater sample has standard composition (i.e.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 18 publications
1
81
0
Order By: Relevance
“…But the practical way used to determine δS A is based on using density measurements [10]. As described by McDougall et al in 2012 [11] from a method suggested by Millero et al [3], δS A can be calculated with the equation:…”
Section: Introductionmentioning
confidence: 99%
“…But the practical way used to determine δS A is based on using density measurements [10]. As described by McDougall et al in 2012 [11] from a method suggested by Millero et al [3], δS A can be calculated with the equation:…”
Section: Introductionmentioning
confidence: 99%
“…However, salinities determined alternatively from both conductivity and chlorinity measurements somewhere in the world ocean may produce mutually inconsistent results. This happens especially if the chemical composition of seawater deviates from that of SSW, such as in the Baltic Sea (Wirth, 1940;Kwiecinski, 1965;Rohde, 1966;Millero and Kremling, 1976;Feistel et al, 2010c) or regionally in the global ocean Tsunogai et al, 1979;Millero, 2000a;Wright et al, 2011;Uchida et al, 2011;McDougall et al, 2012;Woosley et al, 2014). In cases when Eqs.…”
Section: Salinity Scalesmentioning
confidence: 99%
“…We came across one problem related to the TEOS-10 thermodynamic framework when applied to isolated eddies. Because the eddies transfer properties nearly unaltered over large distances the application of a regional (observing location) correction for the determination of the S A (McDougall et al, 2012) seems questionable. In the case of the surveyed eddy the impact was tested by applying the ion composition correction from 17 • W (eddy origin) and compared with the correction at the observational position, more than 700 km to the west, and a salinity difference of a little less than 0.001 g kg −1 was found.…”
Section: Glider Sensor Calibrationsmentioning
confidence: 99%